Los Angeles Dodgers vs. Montreal Expos Baseball Game at Dodger Stadium - Watkins, Howard::::::::: (1989)
Scoreboard shows Dodger won 4-3 in 9 innings; clock at 9:51 pm; right field stands totally empty